(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
The article highlights the inclusion of Rda (early childhood autism) in the schizophrenic defect of the psyche and its special place, its distinction from all developmental anomalies in terms of its clinical manifestations and the greatest complexity and inconsistency with the psychological structure of the disorder, the stages of normative speech development, the causes of speech disorders in children with autism, the fact that their symptoms are primarily based on social factors, what factors should be paid attention to when organizing a correctional work system, and the specific features of children with autism